Environmental and social challenges for urban subway construction: An empirical study in China. Issue 3 (April 2015) - Xue, Xiaolong; Zhang, Ruixue; Zhang, Xiaoling; Yang, Rebecca Jing; Li, Hong
Abstract With rapid urban development in China, investments on subway projects are increasing. Although the type of projects can relieve transportation pressure in cities and make citizen's life easier, it raises many environmental and social problems during the construction process, in particular, problems about residents' daily life. Therefore, it is necessary to identify key environmental and social impacts of urban subway constructions and adjust construction programs and urban transportation programs to reduce negative impacts on citizen's daily life during construction. This paper analyzes the key factors for measuring environmental and social influences of subway construction and their interrelationships by using structural equation modeling (SEM) method. Four major impact factors are identified, namely, the impact on residents' travel, transportation, environment and daily life. Then some suggestions are made accordingly. These findings can be used as references for governments, contractors and other parties to develop more rational construction programs to minimize negative impacts of subway construction in urban development.